Financial Information System on Marketplace XYZ Based on PSAK 2025 Using the Laravel Framework - Kelvin Effendy; Agus Hermanto (Green Publisher Indonesia, 2026)
This research is based on the complexity of financial management in the XYZ marketplace, which still relies on manual processes, resulting in a high risk of errors, time inefficiencies, and inaccuracies in financial statements. This research aims to develop a financial information system based on PSAK 2025 with accounting automation to improve the efficiency and accuracy of financial data management. This research uses a qualitative prototyping method, comprising requirements gathering, module prototyping (COA, journals, AP, AR, financial reports), expert evaluation, refinement, and dummy data testing. Primary data comes from interviews with accounting experts, while secondary data comes from literature and documentation. The results showed that the system managed to achieve 100% recording accuracy, reduce reporting time by 99.9% (from 8 hours to under 5 seconds), and meet the PSAK 2025 standards in account classification, revenue recognition, and financial report presentation. The system also implements Role-Based Access Control (RBAC) for data security and automated transaction processing for typical marketplace transactions. This research contributes to the provision of a fully integrated, real-time, and audit-ready financial information system that can serve as a reference for similar digital platforms in Indonesia.